ASSESSMENT OF RURAL YOUTH ADOPTION OF CASSAVA PRODUCTION TECHNOLOGIES IN SOUTHWESTERN NIGERIA - Julius Olatunde AYINDE; Samuel Oluwaseun OLATUNJI; Abiodun Oladayo AJALA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This study assessed rural youth’s adoption of cassava production technologies in Southwestern, Nigeria and determined the extent of usage of the technologies among them. A multistage sampling procedure was used to select 135 respondents. A well structured interview schedule was used to elicit information from the respondents. The data collected were analyzed using descriptive and inferential statistics. The results showed that the average age of rural youths that were engaging in cassava production in the study area was 29 ± 2.6 years with average farm size of 2.5 ± 0.3 hectares. Also, household size (r = 0.249; P ≤ 0.01) and extent of usage of the technologies (r = 0.363, p ≤ 0.01) shows significant relationship with level of adoption of the technologies at 0.01 while age (r = 0.097; P ≤ 0.05) and years of former education (r = 0.181; P ≤ 0.05) were significant at 0.05. It was concluded that the extent of usage of the technologies in the communities affect the rate of adoption positively and this might enhance the positive perception of youths on cassava production thereby ensure food security in the study area.